Nigella Christmas : food, family, friends, festivities - Lawson, Nigella, 1960- (Chatto and Windus, 2008)
Nigella Christmas comprises reliable, practical, easy-to-follow recipes and reassuring advice about planning and cooking ahead, presented in a gorgeous glittering package which will make this the ultimate gift to yourself and for family and friends. Illustrated with over 250 fabulous full-colour photographs by Lis Parsons (photographer of the bestselling